Identifikasi Keterampilan Berbahasa Siswa Kelas III dalam Pembelajaran Bahasa Indonesia - Ahmad Fahmi Saifudin; Wagiran Wagiran; Haryadi Haryadi (Journal of Elementary School (JOES), 2022)
Language is a communication tool between humans to be able to share experiences, learn from each other and improve intellectual abilities. To be able to communicate well, it is necessary to master the 4 language skills, namely listening skills, speaking skills, reading skills and writing skills. Based on the results of observations and interviews, a problem was found, namely the low mastery of language skills by the third grade students at SDN 2 Plantaran. Factors that cause these problems come from students who lack interest and motivation in following Indonesian language learning. This can be seen from the results of observations that have been made by researchers during the implementation of learning. This study aims to describe how the implementation of Indonesian language learning for class III students, describe the factors that influence difficulties in mastering language skills, and describe strategies as a solution to overcome the problems of class III students' difficulties in mastering language skills. This research was conducted through descriptive qualitative research. Data collection techniques used are interviews, observation and documentation. Keywords: Indonesian Language Learning, Language Skills